A concise review of the brown seaweed Sargassum thunbergii — a knowledge base to inform large-scale cultivation efforts - Liu, Fu-Li (2021)
Sargassum thunbergii is a brown macroalga endemic to the northwest Pacific. It plays important ecological roles in the structure and maintenance of coastal marine ecosystems. The bioactive compounds extracted from S. thunbergii have been extensively documented for potential use in anti-obesity, anti-inflammatory activity, anti-tumor, anti-oxidant and aquacultural drugs. The species is edible and contains relatively high levels of proteins, minerals and several types of amino acids. The present work compiles recently published literature on S. thunbergii, with particular focus on cultivation efforts in China, including the breeding of seedlings and cultivation at sea. A concise review of possible applications is given. Distribution, range shifts associated with past climate change, population genetic structure and connectivity, life history, reproduction and development are all detailed. The review provides important guidelines for future large-scale farming of S. thunbergii. This will help aquaculturalists (phyconomists) to meet the expected increases in demand by industrial users. It will also help to conserve natural populations which may be declining due to destructive harvesting and rapid ocean changes.